2020
DOI: 10.1039/c9tb01795j
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of indomethacin–methotrexate in situ hydrogel for the synergistic treatment of rheumatoid arthritis

Abstract: Intra-articular injection of a temperature-sensitive hydrogel containing D-NPs formed by PEI-SS and IND and MTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…In addition, the authors assessed the formulation toxicity, liver and kidney function of treated rats and found that the drug-loaded hydrogel did not appear to have side effects on liver or kidney function. Overall, this work demonstrated the synergistic effect of indomethacin and methotrexate loaded in D-NGel, effectively improving the rheumatoid arthritis conditions by releasing these drugs in a controlled manner into the joint tissue(98).Other researchers, Lu et al (2013) (97), evaluated the effect of the hydrogel containing hyaluronic acid and doxycycline (HA-DOX hydrogel) through intra-articular injections using osteoarthritis rabbit model. The authors hypothesised that combining HA and doxycycline in the hydrogel may provide a synergistic effect through the anti-inflammatory and analgesic effect of doxycycline, hyaluronic acid and the lubricant effect of the hydrogel.…”
mentioning
confidence: 72%
“…In addition, the authors assessed the formulation toxicity, liver and kidney function of treated rats and found that the drug-loaded hydrogel did not appear to have side effects on liver or kidney function. Overall, this work demonstrated the synergistic effect of indomethacin and methotrexate loaded in D-NGel, effectively improving the rheumatoid arthritis conditions by releasing these drugs in a controlled manner into the joint tissue(98).Other researchers, Lu et al (2013) (97), evaluated the effect of the hydrogel containing hyaluronic acid and doxycycline (HA-DOX hydrogel) through intra-articular injections using osteoarthritis rabbit model. The authors hypothesised that combining HA and doxycycline in the hydrogel may provide a synergistic effect through the anti-inflammatory and analgesic effect of doxycycline, hyaluronic acid and the lubricant effect of the hydrogel.…”
mentioning
confidence: 72%
“…Yin and colleagues developed thermo-responsive in situ-forming hydrogels via physical crosslinking with a rapid gelation time of 15 s initiated closer to body temperature. The drug-loaded hydrogels show the sustained release of NPs co-loaded with indomethacin (IND) and methotrexate (MTX) over 72 h for the treatment of rheumatoid arthritis [27]. In this instance, the gelation rate of physical crosslinking is influenced by polymer and drug compositions, as well as collective physiological responses.…”
Section: In Situ-forming Hydrogelsmentioning
confidence: 99%
“…Relieving swelling, reducing inflammation, and reversing the damage of articular cartilage can be achieved at the same time by injecting the hybrid hydrogel platform into the diseased joint [126]. Yin et al [127] designed a nanoparticle hybrid hydrogel platform for the synergistic treatment of RA. In this study, the hybrid system was made of temperature-sensitive hydrogel (D-NGel) and nanoparticles (D-NPs), which were loaded with indomethacin (IND) and MTX-specifically, the long-acting hydrogel formed after intra-articular injection.…”
Section: Micro-/nanoparticle Hybrid Hydrogel Platform In Symptomatic Treatmentmentioning
confidence: 99%